ASV lobiju ietekme uz ārpolitiku - Gukova, Inesa (Latvijas Universitāte, 2009)
Bakalaura darbā „ASV lobiju ietekme uz ārpolitiku” ir veikta analīze par ASV lobiju ietekmi uz tās ārpolitiku. Interešu grupas pauž, ka tās pārstāv dažādu grupu intereses, tomēr tās arī pārstāv lielus finanšu resursus, tāpēc rodas jautājums, vai šīs grupas vai to nauda būt pietiekami ietekmīgas, lai iespaidotu ASV ārpolitiku, piemēram, uzsākot karu? Bakalaura darba mērķis bija analizēt lobiju ietekmi pār lēmumu pieņemšanas procesu, un tas ir sasniegts. Darba gaitā tika izpētīts, ka lobiju ietekme uz ASV ir liela un tā iespaido arī tās ārpolitiskos lēmumus. Iespaidīgākie lobiji ir enerģētikas, ieroču un Izraēlas lobiji, un tie ir iespaidojuši arī lēmumu pieņemšanas procesu attiecībā uz iebrukumu Irākā. Bakalaura darbā ir izvirzīta hipotēze: Ja lobijiem ASV politikā nebūtu tik lielas ietekmes uz lēmumu pieņemšanas procesu, lēmums uzbrukt Irākai 2002.gadā netiktu pieņemts. Darba gaitā tika analizēta konkrētu interešu grupu ietekme attiecībā uz iebrukumu Irākā. Darba izstrādes gaitā lielākoties tiks izmantota salīdzinošās novērtēšanas metodoloģijas pieeja, lai analizētu konkrētu interešu grupu ietekmi Irākas invāzijas sakarā. Tāpat tiks pētīta literatūra, kurā ir iztirzāta bakalaura darba problemātikas būtība, un rezultātā tiks veidota analīze un salīdzinājums, novedot pie darba mērķa sasniegšanas. Analizējot ASV lobiju ietekmi ārpolitiku, ir pierādījies, ka, ja lobijiem ASV politikā nebūtu tik lielas ietekmes uz lēmumu pieņemšanas procesu, lēmums uzbrukt Irākai 2002.gadā netiktu pieņemts.

In bachelors work „Group of benefits influance over USA foreign policy” there is analysis of group of benefits influance over USA. Powerful groups of benefits are considered to represent interesets of some particular group, however, they are also representing a large custodians of financial resources, therefor appears question, can these groups or theire money be strong enought to have an effect on such of decisions in foreign policy, like inception of war? The purpose of bachelors work is analysis of group of benefits influance over process of decision in such a question like invasion in Iraq, and mountened purpose is been reached. In working process there is been salient the powerfulest lobies in context of war in Iraq and also ther`s been researched the size of role, wich is being played by energetic industry, weaponry industry and lobies of organizations in Israel. During the work, ther`s been made an analysis of overspreads between group of benefits and functions of political parties in USA, and influance of group of benefits over the George Bush`s administration. In the paper there is also sightworthy prehistory of war and posibble reasons for invasion of USA in Iraq, thereby looking for answeres to such questions like, why there were elected the concrete moment for begining of war and what was it`s political context? At the conclusion of work, there are solutions of group of benefits influence over George Bush`s administrations decision to intrude in Iraq. In bachelors work there`s purposed hypotesis, if the lobbyists in US politics would not be such big impact on decision-making process, the decision to attack Iraq in 2002 would not been taken. During the process, to analyse concrete group of benefits influence over invasion in Iraq, there`s been used comparative assessment methodology. Thereby, this is how are analysed literature and publications about capture of government in context of group of benefits, theire actions in Washington and relations with Bush`s administration, as well as theire influance over invasion in Iraq. Literature and publications, were examinated similary. Analysing group of benefits influence over USA foreign politicts in context of war in Iraq, is been infered, that if the lobbyists in US politics would not be such big impact on decision-making process, the decision to attack Iraq in 2002 would not been taken.
Group of benefits influance over USA foreign policy
Keywords: Politikas zinātne (politoloģija)